Biased signaling at mu opioid receptor splice variants - Pan, Ying-Xian (Henry Stewart Talks, 2020)
Extensive alternative pre-mRNA splicing of the mu opioid receptor gene (OPRM1), Distinct intracellular C-terminal tails in different full-length 7TM C-terminal variants, Distinct in vivo functions of several C-terminal tails, In vivo truncation of C-terminal tails encoded by E7 affects morphine tolerance and reward, In vivo truncation of C-terminal tails encoded by E4 affects morphine tolerance and dependence